Modeling and Simulation of Fog and Edge Computing Environments Using iFogSim Toolkit - Mahmud, Redowan; Buyya, Rajkumar (Fog and Edge Computing, 2019)
This chapter focuses on delivering a tutorial on iFogSim. iFogSim simulation toolkit is developed upon the fundamental framework of CloudSim. CloudSim is one of the wildly adopted simulators to model cloud computing environments. The chapter briefly discusses the iFogSim simulator and its three basic components: physical components, logical components, and management components. It explores high‐level steps to model and simulate fog computing environment. The chapter revisits the way of installing iFogSim and provides a guideline to model fog environment. Some fog scenarios and their corresponding user extensions are included in the chapter. Finally, the chapter concludes with the simulation of a simple application placement policy and a case study in smart healthcare. The case study includes a schematic illustration of the system architecture and application model for the Internet‐of‐Things (IoT)‐enabled healthcare solutions.